2010
DOI: 10.1074/jbc.m109.038638
|View full text |Cite
|
Sign up to set email alerts
|

GADD45β Enhances Col10a1 Transcription via the MTK1/MKK3/6/p38 Axis and Activation of C/EBPβ-TAD4 in Terminally Differentiating Chondrocytes

Abstract: GADD45␤ (growth arrest-and DNA damage-inducible) interacts with upstream regulators of the JNK and p38 stress response kinases. Previously, we reported that the hypertrophic zone of the Gadd45␤ ؊/؊ mouse embryonic growth plate is compressed, and expression of type X collagen (Col10a1) and matrix metalloproteinase 13 (Mmp13) genes is decreased. Herein, we report that GADD45␤ enhances activity of the proximal Col10a1 promoter, which contains evolutionarily conserved AP-1, cAMP-response element, and C/EBP half-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 82 publications
2
44
0
Order By: Relevance
“…Plasmid Construction-The Ϫ1602/ϩ20-MMP13-Luc promoter construct was described previously (30). The MMP13 promoter sequences spanning Ϫ1007/ϩ20 and Ϫ273/ϩ20 bp were prepared by PCR using the pCAT-MMP13 promoter construct as template as described (30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmid Construction-The Ϫ1602/ϩ20-MMP13-Luc promoter construct was described previously (30). The MMP13 promoter sequences spanning Ϫ1007/ϩ20 and Ϫ273/ϩ20 bp were prepared by PCR using the pCAT-MMP13 promoter construct as template as described (30).…”
Section: Methodsmentioning
confidence: 99%
“…Expression vectors encoding ELF3, ELF5, EHF, RUNX2, c-Fos, and c-Jun have been described (27,30). Vectors encoding JNK, ERK1/2, p38, MKP1, and the constitutively active MAP2K MKK7, MKK6, and MEK1 were purchased from Addgene and described elsewhere (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NFκB signaling strongly induces the expression of transcription factors such as HIF2α [Yang et al 2010] and Elf3 [Otero et al 2012], which in turn bind to and activate MMP13 and other gene promoters (Figure 1). The stress-induced MAPK pathways, including the ERK, c-Jun N-terminal kinase (JNK) and p38 MAPK cascades, coordinate the induction and activation of gene expression through transcription factors such as activator protein 1 (cFos/cJun), ETS, C/EBPβ, and Runx2 [Goldring and Sandell, 2007;Long and Loeser, 2010;Tetsunaga et al 2011;Tsuchimochi et al 2010]. Induction of both ADAMTS4 and 5 requires Runx2 [Tetsunaga et al 2011], and NFκB and HIF2α [Yang et al 2010] mediate ADAMTS4 upregulation, whereas MMP-13 induction requires all three transcription factors.…”
Section: Inflammation and Mechanical Stress In Osteoarthritismentioning
confidence: 99%
“…Houvras et al (Houvras and others 2000) found that wild type (wt) BRCA1 bound ATF1, causing transcription of a luciferase reporter gene. Such a finding strongly suggests (Ishiguro, 1997) StAR (Clem, 2005) Thrombospondin 1 (Ghoneim, 2007) Collagen, type X, α1 (Tsuchimochi, 2010) MMP13 (Tsuchimochi, 2010) Cyclin A (van Dam, 2001) Aromatase (Deb, 2006) MMP2 (Song, 2006) COX2 (Subbaramaiah, 2002) Cyclin D1 (Lee, 1999) Maspin (Maekawa, 2008) IFNγ (Xue, 2005) FoxP3 Fibronectin (Yin, 2010) Snail (Yin, 2010) Twist (Yin, 2010) Slug (Yin, 2010) av integrin (Yin, 2010) β6 integrin (Yin, 2010) E-cadherin (Yin, 2010) Increased malignancy Osteocalcin ( www.intechopen.com very few studies have been performed on the role of ATF1 in breast cancer. Important future studies will elucidate the effects of ATF1 on immunity and hormone synthesis in both normal and neoplastic breast cells, as well as its role in breast cancer in vivo.…”
Section: Atf1mentioning
confidence: 99%